2010
DOI: 10.1038/onc.2010.574
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.5 enhances breast cancer cell invasiveness by increasing NHE1-dependent H+ efflux in caveolae

Abstract: Na V 1.5 sodium channels enhance the invasiveness of breast cancer cells through the acidic-dependent activation of cysteine cathepsins. Here, we showed that the Na þ /H þ exchanger type 1 (NHE1) was an important regulator of H þ efflux in breast cancer cells MDA-MB-231 and that its activity was increased by Na V 1.5. Na V 1.5 and NHE1 were colocalized in membrane rafts containing caveolin-1. The inhibition of Na V 1.5 or NHE1 induced a similar reduction in cell invasiveness and extracellular matrix degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(212 citation statements)
references
References 26 publications
13
199
0
Order By: Relevance
“…Interestingly, we have shown in this study that NHE7-overexpression facilitates tumor invasion, cell-overlay and tumor formation in vivo. NHE1 is known to facilitate tumor invasion by acidifying the local pH and thereby activating pH-sensitive enzymes that degrade the extracellular matrix (9, [40][41][42][43][44][45]. In agreement, we also showed that overexpression of NHE1 in MDA-MB-231 cells enhances cell invasion (N1 in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, we have shown in this study that NHE7-overexpression facilitates tumor invasion, cell-overlay and tumor formation in vivo. NHE1 is known to facilitate tumor invasion by acidifying the local pH and thereby activating pH-sensitive enzymes that degrade the extracellular matrix (9, [40][41][42][43][44][45]. In agreement, we also showed that overexpression of NHE1 in MDA-MB-231 cells enhances cell invasion (N1 in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In cancer cells, overexpression of VGSCs and/or their upregulation has been observed. In particular, the Nav1.5 channel type correlates with cancer cell invasion (20)(21)(22). Although it seems that the neonatal isoform of Nav1.5 channel may be a potential target for cancer therapy, so far the mechanisms regulating its expression and its functional activity in cancer cells have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of functional Na v , thus appears to accelerate development of cancer metastases in a variety of carcinomas. However, details of the downstream effects of Na v (Brisson et al, 2011;Gillet et al, 2009) and the cellular mechanism(s) that regulate their expression and activity in metastatic cells remain unclear (Ding et al, 2008;Uysal-Onganer and Djamgoz, 2007).…”
Section: Introductionmentioning
confidence: 99%